Supportive Care Needs of Women with Breast Cancer: A Systematic Review - Irfan Wabula; Esty Yunitasari; Andri Setiya Wahyudi (Universitas Airlangga, 2020)
Introduction: An understanding of supportive care needs is essential to achieve good quality care for women with breast cancer. This concept defines the needs of cancer patients in relation to the physical, emotional, psychological, social, informational and spiritual domains since the start of their journey through diagnosis, treatment, survivorship, palliative care and the grief process.Methods: This study was conducted to explore the unmet supportive care needs of women with breast cancer. Databases were searched in the journals using pre-determined keywords such as ‘supportive care needs’, ‘breast cancer’ and ‘woman’. The databases used were Scopus, Pro Quest, Science Direct and EBSCO. The search was limited to journals published in the period 2014-2020. Out of the 189 nursing journals initially found, 16 journals were selected that met all of the eligibility criteria. Eight studies used a cross-sectional design.Results: Most of the breast cancer patients were in the post-diagnosis phase and had survived. More than 50% of the journals reported that the needs of breast cancer women were going unmet. The predictors of a higher level of need among the breast cancer patients are age, social support and information. The most prevalent unmet needs among the women with breast cancer were found to be in the health system and related to information. Conclusion: Future research should focus on improving the education and psychological support programs available to provide for the unmet supportive care needs of patients newly-diagnosed with breast cancer. This can provide high quality care for them.